A New Earth: Awakening to Your Life's Purpose - Eckhart Tolle (Penguin Books, 2006)
Eckhart Tolle's first full length book in eight years will be a cornerstone for personal spirituality and self-improvement for years to come. Taking off from the introspective work he began with The Power of Now, the number one bestseller that has sold millions of copies worldwide, Tolle provides the spiritual framework for people to move beyond themselves in order to make this world a better, more spiritually evolved place to live. Shattering modern ideas of ego and entitlement, self and society, Tolle lifts the veil of fear that has hung over humanity during this new millennium, and shines an illuminating light that leads to happiness and health that every reader can follow.